Type and Function of Diarki in Traditional Wedding Ceremonies in Rumahlewang Besar Village - Taliak, Bertha Ketsia; Maspaitella, Martha; Tabelessy, Novita (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research study analyzes the varieties and roles of diarki in traditional wedding ceremonies in the hamlet of Rumahlewang Besar, Pulau Wetang District, West Southwest Maluku Regency. This research employs a qualitative descriptive method, focusing on the words and sentences present in the diarki during traditional wedding ceremonies. This study employs five data gathering techniques: observation, interviews, recording, field notes, and documentation. The employed data analysis procedures include data reduction, data presentation, and conclusion formulation. This study's findings reveal the existence of five diarki employed in the traditional wedding ritual of Rumahlewang Besar hamlet, located in the Pulau Wetang District of West Southwest Maluku Regency. Among the five diarchies present in the traditional wedding ceremony, one category of folk song, specifically the lyrical folk song, does not constitute a true diarki: folk songs pertaining to courtship and matrimony. Singing at traditional wedding ceremonies has two functions: it validates cultural norms and institutions, and it acts as a projective system that reflects communal desires. Among these two purposes, the predominant one is the validation of cultural norms and institutions.